TOC, TIC, TN and TS contents and stable isotope signatures (δ13C of TOC, δ15N, δ34S) of fine-grained saltmarsh deposits of the barrier island Spiekeroog at the southern North Sea Coast - Thomas Pollmann; Michael Ernst Böttcher; Luise Giani (PANGAEA, 2021)
The dataset compiles total organic carbon (TOC), total inorganic carbon (TIC), total nitrogen (TN) and total sulfur (TS) contents and stable isotope signatures (δ13C of TOC, δ15N, δ34S) of fine-grained deposits (clay, loam) over sandy subsoils of the saltmarsh of the barrier island Spiekeroog at the southern North Sea coast. Sampling was performed in September 2016 along three transects spanning from the high saltmarsh to the pioneer zone. At each sample point, soil samples were taken from the first 5 cm of the upper part (top samples) and from the deepest 5 cm of the lower part (bottom samples) of the fine-grained deposit. If the fine-grained deposit layer had a thickness < 10 cm, only one bulk soil sample (single samples) was taken for the depth range equal to the deposit thickness. Samples were ground to fine powder. TIC was measured on oven-dried samples coulometrically with an Analytik Jena multi EA 4000 analyzer. The total carbon (TC), TN, and TS were analyzed using a Thermo Scientific Flash EA Isolink Elemental Analyzer. The TOC contents were calculated as the difference between TC and TIC. TOC, TN, and TS contents are reported based on the original dry mass. For isotope analysis, dried and homogenized samples were weighed in tin cups and combusted in a Thermo Scientific Flash EA Isolink Elemental Analyzer, connected to a Thermo Finnigan MAT 253 gas mass spectrometer via a Thermo Conflo IV split interface. The δ13C values of TOC were measured after decalcification of the ground powders with p. a. grade HCl. The TN and δ34S analysis were carried out on a separate aliquot of sample powder. The isotope results are given in the conventional δ-notation.